Return to work following disabling occupational injury – facilitators of employment continuation - Young, Amanda E. (Scandinavian Journal of Work, Environment & Health, 2010)
' ' OBJECTIVE ': 'Return to work following occupational injury is an important rehabilitation milestone; however, it does not mark the end of the return-to-work process. Following a return to the workplace, workers can experience difficulties that compromise their rehabilitation gains. Although there has been investigation of factors related to a return to the workplace, little attention has been paid to understanding what facilitates continued return-to-work success as this paper aims to do. ' ' METHODS ': 'This study used data gathered during one-on-one telephone interviews with 146 people who experienced a work-related injury that resulted in their being unable to return to their pre-injury job, but who returned to work following an extended period of absence and the receipt of vocational services. ' ' RESULTS ': 'Numerous return-to-work facilitators were reported, including features of the workers’ environmental and personal contexts, as well as body function, activities, and participation. Influences that stood out included a perception that the work was appropriate, supportive workplace relationships, and a sense of satisfaction/achievement associated with being at work. ' ' CONCLUSIONS ': 'The findings support the contention that initiatives aimed at improving return-to-work outcomes can go beyond the removal of barriers to include interventions to circumvent difficulties before they are encountered. Together with providing ideas for interventions, the study’s findings offer an insight into research and theoretical development that might be undertaken to further the understanding of the return-to-work process and the factors that impact upon it.
Keywords: disablement; employment continuation; injury; long-term sickness absence; occupational injury; rehabilitation; return to work; return-to-work; sickness absence; vocational rehabilitation